TERTRAIS, B. & PAPIN, D. (2018). Atlas de las fronteras. Muros, conflictos, migraciones. Cátedra: Madrid. - Oriol Navarro Erausquin; Lucas Vaquero Álvarez (Daimon)
Reseña de: TERTRAIS, B. & PAPIN, D. (2018). Atlas de las fronteras. Muros, conflictos, migraciones. Cátedra: Madrid.